STUDYING OF INFLUENCE OF WAYS OF PROCESSING ON EFFICIENCY OF EXTRACTION OF PAINTING PIGMENTS FROM AN AMARANTH - Uazhanova, Raushangul; Aizhan, Nurmatova; Saken, Baimuratov; Bakytgul, Kaliyeva; Gulaina, Zeynel; Alima, Kadyrbayeva (European Scientific Journal, ESJ, 2014)
In this article the study of methods of treatment is shown on efficiency of extraction of dyeings pigments from a plant amaranth. As a result of the got results the ground of receipt of dye is given from an amaranth by water solution and extracting by an ethyl spirit, study of functionally-technological properties of dye in different environments, that safe-health people, and also safely to use in the production of food products,answering the necessary requirements of Law on safety of food products. An analysis is Given, that dye from an amaranth possesses high stability to the change of Ñ€Ð environment and stability to influence of temperatures and that color forms addition Amaranth can be used for preparation of products, the technological process of production of that envisages heat treatment not exceeding 70Â°Ð¡.